2018
DOI: 10.1021/acs.jafc.8b05101
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Differential Responses in the Root-Knot Nematode Meloidogyne incognita to Tomato Root Exudate Cytokinin, Flavonoids, and Alkaloids

Abstract: Root exudates of plants mediate interactions with a variety of organisms in the rhizosphere, including root-knot nematodes (RKNs, Meloidogyne spp.) We investigated the responses of the motile stage second-stage juveniles (J2s) of Meloidogyne incognita to non-volatile components identified in the root exudate of tomato. Using stylet thrusting, chemotaxis assays, and chemical analysis, we identified specific metabolites in the root exudate that attract and repel J2s. Liquid chromatography quadrupole time-of-flig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 53 publications
5
64
0
2
Order By: Relevance
“…It's a reasonable deduction that concentrations of DHA used in this study reflect the concentration of DHA in wheat root exudates. It was found that like other attractants for nematodes reported [16,41], the response of H. avenae to DHA was concentration-dependent, because attraction levels of H. avenae to DHA with concentrations of 0.1 mg/L, 0.5 mg/L and 1.0 mg/L were different. Whether DHA plays roles in the orientations of plant for other nematodes remains unknown.…”
Section: Plos Onementioning
confidence: 85%
“…It's a reasonable deduction that concentrations of DHA used in this study reflect the concentration of DHA in wheat root exudates. It was found that like other attractants for nematodes reported [16,41], the response of H. avenae to DHA was concentration-dependent, because attraction levels of H. avenae to DHA with concentrations of 0.1 mg/L, 0.5 mg/L and 1.0 mg/L were different. Whether DHA plays roles in the orientations of plant for other nematodes remains unknown.…”
Section: Plos Onementioning
confidence: 85%
“…With this perspective, it is interesting that repellent compounds have been identified in economically important host plants, where root knot nematodes are particularly problematic, e.g. tomato plants (Yang et al, 2016;Kirwa et al, 2018). In horticultural production, grafting is becoming a common alternative to lengthy breeding for pathogen resistance.…”
Section: Application Of Root Metabolites In Nematode Management-challmentioning
confidence: 99%
“…In vitro experiments have shown that several common flavonoids show (limited) anti-nematode activity: kaempferol is inhibitory to the hatching of R. similis eggs while kaempferol, quercetin, and myricetin are both repellent and somewhat nematistatic (but not nematicidal) to M. incognita juveniles (Wuyts et al, 2006b). The effect of flavonoids on nematode behavior, however, is complex: they can either attract or repel M. incognita juveniles depending on their molecular structure and concentration (Kirwa et al, 2018). Flavonoids have been most extensively studied in relation to plant-nematode interactions in the Fabaceae family, whose members produce various isoflavonoids and pterocarpans (phytoalexins derived from isoflavonoids via coupling of the isoflavonoid B ring and 4-one position) in response to infection.…”
Section: Flavonoidsmentioning
confidence: 99%